In Vitro Total Phenol, Antioxidant and Antibacterial Activities of Tulbaghia violacea Crude Extracts (African Journal of Biomedical Research, 2023)
This study was designed to assess the antibacterial activity of Tulbaghia violacea, to evaluate its total phenol activity, antioxidant activity, and antibacterial activity. the antioxidant and antibacterial activities were assessed using the 2,2-diphenyl-1-picrylhydrazyl assays and p-Iodonitrotetrazolium chloride assay respectively. The total phenolic evaluation found that the aqueous and the bulb methanol/dichloromethane extract contained the lowest amount of phenolics, and leaf extract had the largest amount. In contrast to the norm, T. violacea extract showed a significant level of antioxidant activity. With several plant extracts, the antibacterial activity produced intriguing results, suggesting that they may be unique to Gram-positive bacteria. The aqueous extracts of the leaf and bulb both exhibited antibacterial action against the Gram-negative bacterium Klebsiella pneumoniae, but not on a Gram-positive organism (Staphylococcus aureus).  At lower concentrations, the extract from water's roots exhibited a comparable result. The elevated concentrations of the root methanol/dichloromethane extract decreased the proportion cell viability of S. aureus more than K. pneumoniae. Dichloromethane bulb and methanol extracts appeared to be efficient on S. aureus. These findings suggest that T. violacea may be an essential extract for developing as an antibacterial agent.
Keywords: Medicinal plant; Total phenol; antioxidant; antibacterial activity